Electrical and Spectroscopic Diagnostics of Atmospheric Pressure DBD Plasma Jet - Roy, NC; Talukder, MR (Journal of Bangladesh Academy of Sciences, 2016)
Atmospheric pressure capillary dielectric barrier oxygen discharge plasma jet is developed to generate nonthermal plasma using unipolar positive pulse power supply. Both electrical and optical diagnostic techniques were used to characterize the produced plasma as functions of applied voltage and gas flow rate. Electrical diagnostics indicated that the discharge frequency decreased with gas flow rate but increased with the applied voltage. Analytical results obtained from the optical emission spectroscopic data revealed the gas temperature, excitation temperature and electron density. Gas temperature was found to decrease with increasing oxygen flow rate but increase linearly with applied voltage. The produced plasma was applied preliminarily to study the inactivation yield of Fusarium oxysporum fungus infected potato samples. Journal of Bangladesh Academy of Sciences, Vol. 40, No. 1, 23-36, 2016